Health and social care workers' professional values: A cross-sectional study - Pakkanen Piiku; Häggman-Laitila Arja; Pasanen Miko; Kangasniemi Mari (SAGE PUBLICATIONS LTD, 2025)
Background: Professional values create a basis for successful collaboration and person-centred care in integrated care and services. Little is known about how different health and social care workers assess their professional values.
Research aim: To describe and compare professional value orientation among different health and social care workers in Finland.
Research design: A quantitative cross-sectional study.
Participants and research context: We carried out an online survey of health and social care workers from 8 March to 31 May 2022, using the Finnish version of the Nurses' Professional Values Scale-3. The data were analysed using descriptive and advanced statistics.
Ethical considerations: Permission was received from all participating organizations and those who completed the survey provided informed consent.
Results: A total of 1823 health and social care workers, representing seven professional groups and students, took part. The overall level of professional values among the participants was relatively high. Commitment to providing patients and clients with equal care was more important than engaging with society and professional responsibilities in the work environment. Professional values were strongest among professionals with higher educational degrees and training in professional ethics. The same was true for workers who received organizational support for ethical practice, were satisfied with their work and had shorter work experience.
Discussion: Our results showed shared professional values among different health and social care workers and students. These results are meaningful for integrated care and services. At the same time, a clear need for strengthening engagement with society and professional responsibilities for developing work environments were identified.
Conclusions: Health and social care workers and students need training in professional ethics and organizational support for ethical practice and work satisfaction to maintain their professional values at different stages of their career.